IMPLIKASI KOMPONEN MAKNA PRODUK SEPEDA MOTOR TAHUN PRODUKSI 2020-2022 PADA PEMBELAJARAN BAHASA INDONESIA DI SMK - Andre Rifki Aji Saputro; Tutut Tugiati (Universitas Muhammadiyah Purwokerto, 2023)
This descriptive qualitative aims to describe the meaning components contained in motorcycle products in the 2020-2022 production year and their implications for Indonesian Language learning at Vocational High Schools. In this study, the data source was brochures of the 2020-2022 production year motorcycles, totaling forty brochures. The data in this study are words and/or phrases which are components of the meanings of color, features, safety, types of brakes, and accessories contained in brochure discourse for the Honda, Yamaha, and Suzuki brands in 2020-2022 production year. The methods and techniques were divided into three: the data collection, the data analysis, and the data analysis results (data presentation) stages. In this study, the data were collected using the listening method with reading and note-taking techniques. In data processing, the method used the referential identity of the dividing key-factors technique (PUP) and distributional methods. The advanced technique used the same interrelational method. In the distributional method, the basic technique used was the Segmenting immediate constituents technique (BUL). The data presentation method used was informal and formal. Based on the results of the analysis and discussion it is known that the meaning components of color, safety, features, brake types, and accessories can show differences between motorcycle brands. The five components of meaning can also show in detail the differences in products and types of motorbikes for each brand. In addition, research on the components of meaning in motorcycle product sales brochures for the 2020-2022 production year can be developed as worksheets in learning the Indonesian language for tenth graders of SMK in the 1st semester, especially for expository texts.